Processing of mayenite electride and its composites in spark plasma sintering - Kuehster, Adam Edward, author; Ma, Kaka, advisor; Weinberger, Chris, committee member; Williams, John, committee member (Colorado State University. Libraries, 2019)
Mayenite electride, as the first inorganic room temperature stable electride, has attracted intensive research interests since the early 2000s due to its great potential in various applications such as catalysts, conductive oxides and thermionic emission materials. Mayenite electride is developed from mayenite, a stoichiometric compound of CaO and Al2O3 (12CaOˑ7Al2O3, referred to as C12A7 hereafter) that has a cubic unit cell with a positively charged lattice framework [Ca24Al28O64]4+ of twelve crystallographic subnano-cages per unit and O2- anions clathrated in the cages to maintain charge neutrality. When mayenite is heat treated in a reducing environment, electrons replace O2- ions clathrated in the cages. The electrons can migrate through the inter-cage framework, leading to the formation of electride (C12A7:e-), an electrically conductive form of C12A7. A variety of methods to make C12A7:e- powder and bulk materials have been investigated in the literature, all of which involve multiple steps and long-time (days to weeks) of heat treatment at high temperatures (>1100 ˚C). Although fundamental knowledge of the structure and functionality of C12A7:e- is advancing in the field, the formation of other calcium aluminate phases during the synthesis of mayenite or its electride has been overlooked. Most of the previous studies also lack detailed microstructure characterization. In addition, monolithic C12A7:e- does not provide continuous ohmic contact due to the destruction of the surface cages during processing, which limits its direct use in thermionic emission devices. To address the aforementioned practical issues and to fill in the fundamental knowledge gap, we investigated the effect of adding different reinforcing particles, including carbon black (CB), Ti, and TiB2, on the formation of C12A7:e- via spark plasma sintering (SPS), with attention particularly paid to address phase formation during the processing. Specifically, preformed C12A7 powder was synthesized via a solid-state reaction and used as the precursor base in SPS to study the effect of additives. In addition, a novel approach using in-situ reaction in SPS was proposed in the present work to significantly reduce the processing time. My research revealed that both Ti and TiB2 effectively reduced C12A7 to its electride phase, C12A7:e-. However, addition of Ti and TiB2 also led to partial decomposition of C12A7 into secondary calcium aluminate phases, primarily Al2O3-rich calcium monoaluminate (CA) and CaO-rich tricalcium aluminate (C3A). Although CB did not effectively reduce C12A7 to C12A7:e-. it did not result in the formation of any secondary calcium aluminate phases. Using Ti foils on the top and bottom of the preformed C12A7 powder in SPS created C12A7:e- with a near-theoretical maximum electron concentration ~ 10^21/cm^3. For the in-situ reaction approach, the chemical homogeneity and size distribution of precursor powders are critical to forming C12A7:e- in the typical processing time frame of SPS (5-15 minutes). The fast heating rate and C-rich environment in SPS increased the CaCO3 decomposition temperature to above 930°C, which is consequential to the calcium aluminate formation reaction. Adding Ti powder lowered the CaCO3 decomposition temperature in SPS and allowed for the formation of C12A7:e- via in-situ reaction sintering. The work function of a 50-50wt% C12A7:e- -Ti composite in this study is ~ 2.6 eV.
Keywords: emission; sintering; thermionic; mayenite; electride; SPS